THE EFFECT OF ELECTRONIC WALLETS (E-WALLET) AND DEBIT CARDS USAGE ON COLLEGE STUDENTS' CONSUMPTION IN SUKABUMI DURING COVID 19 PANDEMIC - Insani, Rahma Arifa; Yuneline, Mirza Hedismarlina (Jurnal Perilaku dan Strategi Bisnis, 2023)
This study aims to determine the effect of electronic wallets and debit cards usage on College student’s consumption Sukabumi during COVID-19 pandemic. The population in this study were active college students in Sukabumi. The data collection technique in this study was through a questionnaire distributed to students who studying in Sukabumi. The method used was descriptive and verification method. The data analysis was through a quantitative approach using the classical assumption test hypothesis testing design, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, T test and F test. The results of this study indicate that the use of electronic wallets (e-wallet) and debit cards have a significant effect on college student consumption in Sukabumi during the COVID-19 pandemic. The use of e-wallet has significant increase due to ease of use and the use of debit cards also have significant increase due to perceived of health. The future research on other indicators on adoption models of e-wallet and debit cards will be needed to enrich the current research.